Prognostic importance of late gadolinium enhancement cardiovascular magnetic resonance in cardiomyopathy. Issue 6 (29th November 2011) - Ismail, Tevfik F; Prasad, Sanjay K; Pennell, Dudley J
Abstract : Cardiovascular magnetic resonance has revolutionised the diagnosis of cardiomyopathy, particularly through the use of late gadolinium enhancement imaging which provides the unique opportunity to assess myocardial fibrosis in vivo. More recently, the prognostic capability of cardiovascular magnetic resonance to predict outcomes has been assessed. Traditional risk markers do not at present adequately predict outcomes in either dilated cardiomyopathy or hypertrophic cardiomyopathy, which are the two most common causes of primary heart muscle disease. Many of these existing markers reflect underlying disease severity. Given the important role fibrosis is thought to play in the pathogenesis and sequelae of these cardiomyopathies, the presence and amount of fibrosis has been proposed as a potential novel risk factor for adverse events. This paper reviews the evidence for late gadolinium enhancement as a prognostic marker in dilated and hypertrophic cardiomyopathy and highlights the challenges ahead.